'Out of house' virtual surgical planning for mandible reconstruction after cancer resection: is it oncologically safe?. Issue 8 (August 2021) - Barry, C.P.; MacDhabheid, C.; Tobin, K.; Stassen, L.F.; Lennon, P.; Toner, M.; O'Regan, E.; Clark, J.R.
Abstract: The purpose of this study was to investigate whether the time delay between 'out of house' proprietary virtual surgical planning (OH-VSP) of the mandibular resection for oral cancer and the actual surgery results in compromised margins and oncological disadvantage for the patient. Outcomes of patients who had OH-VSP of their mandibular resection and reconstruction were compared with those of patients who had the same surgery using a conventional non-VSP approach. The groups were similar in patient demographics, tumour stage and size, nodal status, and reconstruction complexity. VSP resulted in a significant reduction in operating time ( P  < 0.01). VSP did not affect bony ( P  = 0.49) or soft tissue ( P  = 0.22) margin status. In summary, VSP reduced the operating theatre time, and despite the time interval between bony resection planning and surgery, there was no compromise to the oncological safety of the operation.